Resorption Controls Bone Anabolism Driven by Parathyroid Hormone (PTH) Receptor Signaling in Osteocytes - Rhee, Yumie (American Society for Biochemistry and Molecular Biology, 2013)
The contribution of remodeling-based bone formation coupled to osteoclast activity versus modeling-based bone formation that occurs independently of resorption, to the anabolic effect of PTH remains unclear. We addressed this question using transgenic mice with activated PTH receptor signaling in osteocytes that exhibit increased bone mass and remodeling, recognized skeletal effects of PTH elevation. Direct inhibition of bone formation was accomplished genetically by overexpressing the Wnt antagonist Sost/sclerostin; and resorption-dependent bone formation was inhibited pharmacologically with the bisphosphonate alendronate. We found that bone formation induced by osteocytic PTH receptor signaling on the periosteal surface depends on Wnt signaling but not on resorption. In contrast, bone formation on the endocortical surface results from a combination of Wnt-driven increased osteoblast number and resorption-dependent osteoblast activity. Moreover, elevated osteoclasts and intracortical/calvarial porosity is exacerbated by overexpressing Sost and reversed by blocking resorption. Furthermore, increased cancellous bone is abolished by Wnt inhibition but further increased by blocking resorption. Thus, resorption induced by PTH receptor signaling in osteocytes is critical for full anabolism in cortical bone, but tempers bone gain in cancellous bone. Dissecting underlying mechanisms of PTH receptor signaling would allow targeting actions in different bone compartments, enhancing the therapeutic potential of the pathway.